Letter : Spanish situation - Harris, Oliver
010-0109-001 Telephone No. 4869. South Wales Miners' Federation. OLIVER HARRIS, GENERAL SECRETARY. 2. St. Andrew's Crescent, Cardiff. 2nd September, 1936. Sir Walter Citrine, National Council of Labour Transport House, Smith Square, London, SW1 Dear Sir Walter, Spanish situation. At a meeting of the Executive Council of the South Wales Miners' Federation today I was instructed to urge upon the National Council of Labour the importance of keeping a watchful eye on the operation of the Neutrality Agreement arrived at by the various Governments, and, if it is found that arms and munitions of war are being supplied to the rebels,a National Conference of all Labour forces should be called with the view of pressing the British Government to assist the Spanish Government against the attacks of the forces of reaction. Yours faithfully, Oliver Harris 292/946/10/117